Design of 8-point DFT based on Rademacher Functions - Zulfikar Zulfikar; Hubbul Walidainy (International Journal of Electrical and Computer Engineering (IJECE), 2016)
This paper presents a new circuit design for 8-point DFT algorithm based on product of Rademacher functions. The design has been adopted from the famous 8-point DFT decimation in time which is mainly constructs of two 4-point and four 2-point DFTs. However, the operation of the design circuit is different. It utilized the advantage of Rademacher functions simplicity. Therefore, the proposed design is constructed form the previous design 4-point DFT which is based on product of Rademacher functions [6]. Some analysis upon number types and internal connections to achieve a more efficient circuit have been conducted. As a result, instead of four, the proposed design requires only three 2-point DFT. Several output results of the design DFT have been removed since they are equal in terms of magnitude, two negative circuit are required as a compensation. Moreover, the previous 4-point DFT has been replaced to the efficient one. This circuit is special designed for non stand alone used, the circuit must be integrated inside the proposed 8-point DFT.